PENGARUH STRUKTUR MODAL DAN EFISIENSI OPERASIONAL TERHADAP PERTUMBUHAN LABA DENGAN PERTUMBUHAN PENJUALAN SEBAGAI VARIABEL MEDIASI - Sultia Linika Sari (Journal of Islamic Studies & Social Science, 2025)
This study aims to analyze the influence of capital structure and operational efficiency on profit growth, with sales growth as a mediating variable, in healthcare companies listed on the Indonesia Stock Exchange and included in the LQ45 index during the period of 2018-2023. The research method used is multiple linear regression to analyze the direct influence of independent variables on the dependent variable, and the Sobel test to analyze the mediation effect of sales growth. The data used is secondary data obtained from the financial statements of companies included in the research sample. The results of the study show that, partially, capital structure and operational efficiency do not have a significant effect on profit growth, while sales growth has a positive and significant effect on profit growth. Sales growth mediates the influence of operational efficiency on profit growth but does not mediate the influence of capital structure on profit growth.